The Algorithm as an Architect of Anxiety: 'Lucid Dreaming' Content Precipitating Acute Somniphobia in a Preadolescent—A Case Report on the 'Digital Pathogen' Phenomenon and Culturally Responsive Mediation - Ni Wayan Saka Rahayu; Putu Risdianto Eka Putra (Scientia Psychiatrica, 2025)
Introduction: The pervasive integration of digital media into pediatric life has shifted the clinical focus from screen time quantity to content quality. Emerging "metaphysical" sub-genres, such as algorithmic "Lucid Dreaming" tutorials, pose unique risks to preadolescents. This case report aims to document a novel presentation of acute sleep anxiety precipitated specifically by "Lucid Dreaming" tutorials. Case presentation: We report the case of a 10-year-old male of Balinese descent presenting with acute sleep onset insomnia (somniphobia), autonomic hyperarousal (resting heart rate 104 bpm), and separation anxiety. The precipitating event was the consumption of "Astral Projection" and "Reality Shifting" content, which the patient, being in the Concrete Operational stage of cognitive development, misinterpreted as a literal biological threat of "soul separation." Assessment via the Spence Children’s Anxiety Scale (SCAS) yielded a score of 46 (98th percentile), indicating severe anxiety. A four-week intervention was implemented, utilizing a Cultural Formulation approach that integrated Balinese spiritual coping with Cognitive Reframing and a Structured Parental Mediation Protocol (restrictive mediation and active co-viewing). Post-intervention analysis showed a statistically significant reduction in SCAS scores to 18 (Reliable Change Index > 1.96) and normalization of sleep onset latency from 140 minutes to 25 minutes. Conclusion: This case identifies specific abstract digital content as a potential cognitive pathogen for vulnerable developmental stages. It highlights the necessity of auditing content quality and validates the efficacy of culturally responsive parental mediation in resolving digitally induced psychopathology.